Metabolic Responses and Resilience to Environmental Challenges in the Sedentary Batrachoid Halobatrachus didactylus (Bloch & Schneider, 1801) - Molina, Juan Manuel (2023)
In the context of climate change, warming of the seas and expansion of hypoxic zones are challenges that most species of fish are, or will be subjected to. Understanding how different species cope with these changes in their environment at the individual level can shed light on how populations and ecosystems will be affected. We provide first-time estimates on the metabolic rates, thermal, and oxygen-related limits for Halobatrachus didactylus, a coastal sedentary fish that lives in intertidal environments of the Northeast Atlantic. Using respirometry in different experimental designs, we found that this species is highly resistant to acute thermal stress (CTmax: 34.82 ± 0.66 ◦C) and acute hypoxia (Pcrit: 0.59–1.97 mg O2 L−1). We found size-specific differences in this stress response, with smaller individuals being more sensitive. We also quantified its aerobic scope and daily activity patterns, finding this fish to be extremely sedentary, with one of the lowest standard metabolic rates found in temperate fish (SMR: 14.96 mg O2 kg−1h−1). H. didactylus activity increases at night, when its metabolic rate increases drastically (RMR: 36.01 mg O2 kg−1h−1). The maximum metabolic rate of H. didactylus was estimated to be 67.31 mg O2 kg−1h−1, producing an aerobic scope of 52.35 mg O2 kg−1h−1 (77.8% increase). The metrics obtained in this study prove that H. didactylus is remarkably resilient to acute environmental variations in temperature and oxygen content, which might enable it to adapt to the extreme abiotic conditions forecasted for the world’s oceans in the near future.